Clientelism, corruption and kleptocratic politics in Bangladesh: a political economy analysis - Moniruzzaman, Md. (Nova Science Publishers, Inc., 2018)
Political clientelism and political corruption reinforce each other. While clientelism either in traditional or modern form remains appreciated in party politics, corruption is considered anathema and anti-systemic. Yet, clientalism and corruption feature prominently in party politics of developing democracies. This largely stems from a weak legal system and strong executive dominance, resulting in clientelism and corruption within a kleptocratic-centred political economy, where a nexus of political, economic and administrative elites exploits and misappropriates already scant resources. In Bangladesh, strong party alignment and political intolerance to opponent parties create a climate of strong political clientelism, leading to rampant state-patronised corruption and misappropriation of public money. Formal and informal legal immunity then institutionalise the practice into a kleptocratic political economy. This article argues that state authorities in Bangladesh consciously patronise the nexus of elites in a kleptocratic political economy, displaying a serious lack of democratic and political accountability.